Sexual and reproductive health in men with spinal cord injury - ARIAN, Iurii; RUSU, Maria; MACHIDON, Daniela; DUMBRAVEANU, Ion (One Health & Risk Management, 2024)
Introduction. Sexual health is a fundamental aspect of overall well-being, quality of life, and a sense of fulfillment. A significant percentage of men with spinal cord injury (SCI) experience ejaculatory issues (95%), poor semen quality (75%), and erectile dysfunction (80%), making it impossible for them to conceive without medical assistance. Material and methods. The bibliographic resources were analyzed and selected from databases such as PubMed, SCOPUS, HINARI, and Web of Science to identify studies on the desired topic. Following the initial research, 128 items were identified, and 32 representative articles were selected for this synthesis article. Results. Damage to the spinal cord can result in partial or complete loss of function below the level of the injury. These injuries lead to impaired ejaculatory and erectile function in addition to reproductive issues, which might include abnormal sperm motility, morphology, and viability, as well as reduced spermatogenesis. Challenges such as loss of bladder and bowel function, changes in physical appearance, spasms, lack of communication, and stereotypes can affect sexual life of men with SCI. Conclusions. Studying sexual dysfunction in disabled men is essential for promoting comprehensive healthcare, supporting mental health, fostering healthy relationships, and advocating for the rights and inclusion of individuals with disabilities. Understanding the mechanisms affecting sexual function in people with SCI is of particular practical interest both in medical practice and in subsequent studies on patients.